Medical Education Department in Medical Schools of Nepal: Opportunities and Challenges - Chandra Rijal, Krishna (Nepal Journal of Medical Sciences, 2026)
In medical schools, universities, or hospitals, a Medical Education Department (MED), also referred to as a Medical Education Unit (MEU) or Center, is a specialized academic unit charged with improving the standard of instruction for health professions. Curriculum development and evaluation, faculty development, assessment and evaluation, educational research, and student support and resources are among MED’s primary duties and functions. The professionalization of instruction and evaluation is one of the most significant advantages that a MED can provide. Other significant opportunities related to MED include strengthened competency-based medical education (CBME), faculty development and capacity building, curriculum innovation and educational research, improved assessment systems, quality assurance, and accreditation support. To reach their full potential, MED must overcome enduring and intricate obstacles that coexist with tremendous opportunities. The main challenges that MED is facing in the recent decade are a lack of trained medical educationists, resistance to change, a lack of institutional support, uneven CBME implementation, and a lack of research output. Therefore, all medical schools should have a functional MED that connects clinical practice and educational theory, guaranteeing that training results in skilled, capable, and socially conscious healthcare professionals.